PENGARUH PENGGUNAAN MEDIA GAMBAR INTERAKTIF TERHADAP KEMAMPUAN MEMBACA NARASI PADA SISWA KELAS II SDN PASI ACEH KABUPATEN ACEH BARAT - Riski Darmawan; Lilis Karlina; Khausar; Syah Mohd Hadiid Thaariq; Hambali (Jurnal Ikhtibar Nusantara, 2026)
This study aimed to determine whether there is a significant effect of using interactive picture media on the narrative reading ability of second-grade students at SD Negeri Pasi Aceh. This research employed a causal research design using a quantitative approach. The population of this study consisted of all 20 second-grade students at SD Negeri Pasi Aceh. The data collection techniques used were observation, tests, and documentation. The research instruments included observation sheets, test sheets, and validation sheets. The findings indicated that the hypothesis testing showed a significant effect of the use of interactive picture media on students' narrative reading ability. The use of interactive picture media contributed 65.3% to the improvement of students' narrative reading ability in Indonesian language learning, while the remaining 34.7% was influenced by other variables that were not examined in this study.